Stare decisis: its development and application in West Malaysia / Mohammad Ramli Ahmad Dahlan - Ahmad Dahlan, Mohammad Ramli (Faculty of Law, 1987)
The sources of Malaysian law can divided into two main forms: written and the unwritten. Unwritten law is that part of law which is not enacted or embodied in any codes or statutes but develops through custom practices and decisions of courts, in this paper, the decisions of the courts will be consider d basically with the doctrine of Stare decisis. The object of this paper is to ascertain the extent to which the English doctrine of precedent is accepted in Malaysia, giving due consideration to the policy of the past and present needs of the courts of Malaysia. It has never been disputed that since the introduction of the doctrine to our country, it has gone through many developments, politically and constitutionally. In determining the doctrine in Malaysia, this paper would be divided into several chapters. Chapter one will discuss the doctrine itself and its early development in England. Chapter Two will highlight the introduction of the doctrine in the Straits settlements, -he application of the doctrine upon the formation of Malaysia will be discussed in Chapter Three with emphasis on the role of Privy . Council as the final Court of appeal then, chapter four will deal with the niera: chial system of precedents as practised today with the Supreme Court as its final court of appeal.